The lion-king in Nahum 2:11–13 [Hebrew 2:12–14] - Snyman, Fanie (Stellenbosch theological journal, 2020)
This contribution investigates the lion metaphor in Nahum 2:11-14 [Hebrew 2:12-14]. Informed by the general theoretical considerations on the working of metaphors, two questions are asked in this contribution: The first question put to the text is to ask whether the portrayal of lion behaviour in the text is correct. The investigation revealed that the description of lion behaviour in the text of Nahum 2:11-13 [Hebrew 2:12-14] differs from what is known about lions. The answer to the first question prompted a second question. The second question is to ask whether the king is portrayed as a lion or is it perhaps the other way around: is the lion seen as a king? Finally, the implications this interpretation will have in understanding this passage will be discussed.